2016
DOI: 10.1212/wnl.0000000000003414
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor encephalitis and other antibody-mediated disorders of the synapse

Abstract: Investigations during the last 10 years have revealed a group of disorders mediated by antibodies against ion channels and synaptic receptors, which cause both neurologic and psychiatric symptoms. In this review, I discuss the process of discovery and immunologic triggers of these disorders, and use anti-NMDA receptor encephalitis to emphasize the importance of understanding the underlying physiopathologic mechanisms in those diseases. A better knowledge of these mechanisms reveals points of convergence with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
170
0
20

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 194 publications
(199 citation statements)
references
References 66 publications
2
170
0
20
Order By: Relevance
“…Naïve cognate antigen‐specific B cells exposed to NMDAR in cooperation with antigen‐specific CD4 + T cells become activated and thus capable of entering the CNS crossing the BBB or the choroid plexus. In the brain, these NMDAR‐specific B cells are thought to undergo further antigen stimulation with clonal expansion, affinity maturation of their antigen receptors, and differentiation into anti‐NMDAR antibody‐producing plasma cells 16. Indeed, a recombinant human anti‐NMDAR monoclonal antibody was recently cloned from intrathecal B cells and showed pathogenic effects in in vitro systems that were similar to those previously reported using CSF of patients 9, 17.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Naïve cognate antigen‐specific B cells exposed to NMDAR in cooperation with antigen‐specific CD4 + T cells become activated and thus capable of entering the CNS crossing the BBB or the choroid plexus. In the brain, these NMDAR‐specific B cells are thought to undergo further antigen stimulation with clonal expansion, affinity maturation of their antigen receptors, and differentiation into anti‐NMDAR antibody‐producing plasma cells 16. Indeed, a recombinant human anti‐NMDAR monoclonal antibody was recently cloned from intrathecal B cells and showed pathogenic effects in in vitro systems that were similar to those previously reported using CSF of patients 9, 17.…”
Section: Introductionsupporting
confidence: 57%
“…In a small subset of patients the anti‐NMDAR immune response is triggered by herpes simplex encephalitis 4. Irrespective of the trigger of anti‐NMDAR encephalitis, data from previous studies suggested an enhancement of the immune response within the CNS, with potential antigen‐driven affinity maturation and clonal expansion of plasma cells 16. This hypothesis was suggested by three findings, (1) a frequent intrathecal synthesis of NMDAR antibodies even early in the disease course,1 (2) biopsy and autopsy material from patients showing brain inflammatory infiltrates containing plasma cells,6, 7 and (3) the better correlation of the course of the disease with CSF antibody titers than with serum antibody titers 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The target molecules can be localized intracellular or extracellular (9, 98). Some of the intracellular antigens are nuclear proteins.…”
Section: Specific Diseasesmentioning
confidence: 99%
“…In many autoimmune and paraneoplastic diseases of the CNS, the B cell response is much better characterized as compared with the T cell response (1, 9). T cell help is required for differentiation of B cells into plasma cells and affinity maturation of antibodies (10, 11).…”
Section: Introductionmentioning
confidence: 99%